Uptake and outcomes of sentinel lymph node mapping in women undergoing minimally invasive surgery for endometrial cancer. (25th January 2022) - Dioun, Shayan; Chen, Ling; Melamed, Alexander; Gockley, Allison; St. Clair, Caryn M.; Hou, June Y.; Khoury‐Collado, Fady; Hershman, Dawn L.; Wright, Jason D.
Abstract: Objective: To examine the patterns and outcomes of sentinel lymph node (SLN) assessment in women with endometrial cancer. Design: Retrospective cohort study. Setting: United States inpatient and outpatient hospital services. Population: Women with endometrial cancer who underwent a laparoscopic or robotic‐assisted hysterectomy. Methods: The Perspective Database from 2012 to 2018 was used. Performance of lymph node dissection was classified as SLN mapping, lymph node dissection or no nodal evaluation. Adjusted regression models were developed to examine the association between SLN mapping and morbidity and cost. Main Outcome Measures: Utilisation rates, morbidity and cost of both lymph node dissection and SLN mapping. Results: Among 45 381 patients, SLN mapping was performed for 7768 patients (17.1%), lymph node dissection was performed for 23 214 patients (51.2%) and no lymphatic evaluation was performed for 14 399 patients (31.7%). SLN mapping increased from 1.8% in 2012 to 35.3% in 2018, whereas the rate of lymph node dissection decreased from 63.5% to 39.1% ( p  < 0.001). Among women who underwent nodal evaluation, residence in the west, White race and use of robotic‐assisted hysterectomy were associated with SLN mapping ( p  < 0.05 for all). The complication rate was 5.9% for SLN mapping, compared with 7.3% in those that underwent lymph node dissection (aRR 0.85, 95% CI 0.77–0.95). The median hospital costs for women who underwent SLN mapping ($10 479) and lymph node dissection ($10 747) were higher than for those who did not undergo nodal assessment ($9149) ( p  < 0.001). Conclusions: The performance of SLN mapping is increasing for endometrial cancer. Compared with lymph node dissection, SLN mapping is associated with lower morbidity. SLN mapping significantly increases the costs compared with hysterectomy alone. Tweetable Abstract: SLN mapping is increasing rapidly for endometrial cancer and is associated with decreased perioperative morbidity. Tweetable Abstract: SLN mapping is increasing rapidly for endometrial cancer and is associated with decreased perioperative morbidity.